Quranic View of the Economic Man - Javad Irvani (آموزه‌های قرآنی)
Economic man here means those aspects of human behaviors and his spiritualities about which economists study. Since the origin of this debate is capitalist economy, its studding in the light of Islamic teachings must be important. In capitalist economic thought, economic man is defined as who “maximizing self-interest”, self-interest confined to the material and sublunary interest and its seeking beside instrumental rationality are regarded as is one of its important characteristics. These definition and characteristics are based on the foundations of the west worldview, including, principles of dualism, naturalism, individualism and utilitarianism. In the Quran, the features and mentioned definition form really the “despicable economic man”. Economic and social crisis of the nineteenth and twentieth centuries and their continuation in the third millennium is also a clear evidence for the economic inefficiency of economic man of capital system. This paper reviews and criticizes briefly the west economic man and its foundations and then expresses the definition and the characteristics of the desirable economic man in view of the Quran.